Comprehensive Physiology 2014
DOI: 10.1002/cphy.c130019
|View full text |Cite
|
Sign up to set email alerts
|

Fever, Immunity, and Molecular Adaptations

Abstract: The heat shock response (HSR) is an ancient and highly conserved process that is essential for coping with environmental stresses, including extremes of temperature. Fever is a more recently evolved response, during which organisms temporarily subject themselves to thermal stress in the face of infections. We review the phylogenetically conserved mechanisms that regulate fever and discuss the effects that febrile-range temperatures have on multiple biological processes involved in host defense and cell death a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 441 publications
0
60
0
7
Order By: Relevance
“…From these observations it was concluded that a fever-like response must have developed 600 million years ago, before the appearance of adaptive immunity but in the setting of established and well-conserved heat shock and innate immune responses (Hasday et al 2014). This evolutionary aspect of fever was frequently used as support for an adaptive value of fever with special emphasis on the fact that such an energetically expensive process has persisted in many groups of organisms for millions of years (Kluger et al 1996).…”
Section: A Classical Viewmentioning
confidence: 97%
See 2 more Smart Citations
“…From these observations it was concluded that a fever-like response must have developed 600 million years ago, before the appearance of adaptive immunity but in the setting of established and well-conserved heat shock and innate immune responses (Hasday et al 2014). This evolutionary aspect of fever was frequently used as support for an adaptive value of fever with special emphasis on the fact that such an energetically expensive process has persisted in many groups of organisms for millions of years (Kluger et al 1996).…”
Section: A Classical Viewmentioning
confidence: 97%
“…The use of behavior to increase body temperature (Tb) has been observed in infected invertebrates including arthropods, annelids and poikilothermic vertebrates (Hasday et al 2014). From these observations it was concluded that a fever-like response must have developed 600 million years ago, before the appearance of adaptive immunity but in the setting of established and well-conserved heat shock and innate immune responses (Hasday et al 2014).…”
Section: A Classical Viewmentioning
confidence: 97%
See 1 more Smart Citation
“…Although on a continuum, mild, moderate, and severe heat stress is defined as a core temperature increase of ≤1.0, 1.0 to 1.5, and ≥1.5 • C, respectively. We do not provide an overview of increased temperature associated with fever as this encompasses a nearly distinct pathological state from passive (external heating) or exertional (exercise induced) etiologies, for reviews, see (192,385). Exertional and passive heat stress, or a combination of the two (strictly described later in: Quantifying heat illness and heat stroke), although separate in etiology, is not uniquely covered in this review.…”
Section: Introductionmentioning
confidence: 96%
“…Textbooks on physiology document that in fever, exogenous and endogenous pyrogens actively shift the thermoregulatory threshold temperature upwards by affecting the thermoregulatory center control. Fever-like responses, including behavioral thermoregulation, are observed in invertebrates having solely innate immune responses, and are speculated to have developed 600 million years ago [43]. Thus, fever acts as a defensive reaction against pyrogens and foreign objects by increasing their clearance, the immune response, and heat-shocking proteins, along with protection against infectious agents [44][45][46].…”
Section: Hyperthermia and Fevermentioning
confidence: 99%